The Biological Standard of Living in the Two Germanies - John Komlos; Peter Kriwy (Center for Economic Studies and ifo Institute (CESifo), 2001)
Physical stature is used as a proxy for the biological standard of living in thetwo Germanies before and after unification in an analysis of a cross-sectionalsample (1998) of adult heights, as well as among military recruits of the1990s. West Germans tended to be taller than East Germans throughout theperiod under consideration. Contrary to official proclamations of a classlesssociety, there were substantial differences in physical stature in East-Germany.Social differences in height were greater in the East amongfemales, and less among males than in the West. Spatial inequality wasgreater in the East than in the West, pointing to the relativelyunderdeveloped nature of the East-German rural sector. The difficultiesexperienced by the East-German population after 1961 is evident in theincrease in social inequality of physical stature thereafter, as well as in theincreasing gap relative to the height of the West-German population. Afterunification, however, there is a tendency for East-German males, but not offemales, to catch up with their West-German counterparts.
Keywords: 330; living standards; welfare; socialism; capitalism; transformation.